THE ILLUSION OF NOT KNOWING IN METACOGNITIVE MONITORING: A BRIEF REVIEW - Avhustiuk , Maria (Psychological Prospects Journal, 2021)
Purpose. The paper is aimed to analyze some key features of the illusion of not knowing in metacognitive monitoring of the learning activity of university students. Among the main conceptions of the influence of the illusion of not knowing on metacognitive monitoring accuracy of the learning activity of university students we tend to study and to analyse different types of the learned information, as well as personal, cognitive, metacognitive, and individual psychological characteristics of students. Moreover, the study may allow to clarifying the phenomenon of the illusion of not knowing and its influence on metacognitive monitoring accuracy measures. Methods. The theoretical and comparative practical methods of studying the illusion of not knowing in metacognitive monitoring of university students have been used in the study. The participants learned texts, statements and pairs of words in Ukrainian. They performed JOLs, aJOLs, RCJs, and aRCJs. Calibration procedure helped to define average indicators of both the illusion of knowing and the illusion of not knowing. Results. The findings indicate that the illusion of not knowing as an error of metacognitive monitoring accuracy (alongside the illusion of knowing) can occur in all types of metacognitive judgments, especially in the prospective judgments of learning. The highest levels of the illusion of not knowing are shown in learning pairs of words, smaller texts of all styles, and in ‘Yes’/‘No’/‘Do not know’ questions. Moreover, the effects of personal, cognitive, metacognitive, and individual psychological characteristics are also allocated. Conclusions. The paper provides an account of the effects of different types of information chosen for the experiment, and of personal, cognitive, metacognitive, and individual psychological characteristics of university students. The findings indicate the illusion of not knowing as an error of metacognitive monitoring accuracy alongside the illusion of knowing. These findings might help to solve the problem of metacognitive monitoring accuracy in the learning activity of university students.